2022
DOI: 10.1172/jci.insight.155260
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of glomerular metabolism and function by podocyte pyruvate kinase M2 in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) arises from systemic and local changes in glucose metabolism and hemodynamics. We have reported that many glycolytic and mitochondrial enzymes, such as pyruvate kinase M2 (PKM2), were elevated in renal glomeruli of DN-protected type 1 and type 2 diabetic patients. Here, mice with PKM2-specific overexpression in podocytes (PPKM2Tg) were generated to uncover its renal protective function as potential therapeutic target, which prevented elevated albumin-creatinine ratio (ACR), mesangial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Several studies have demonstrated that m 6 A modulators (e.g., METTL3 and WTAP) affect tumor glucose metabolism by regulating glycolytic enzymes (Warburg effect) to promote proliferation [ 58 60 ]. The glycolytic pyruvate kinase isoenzyme PKM2 (a glycolytic rate-limiting enzyme) is expressed in a variety of cells, particularly tumor cells [ 61 ]. The m 6 A eraser, FTO, accelerates translation and promotes malignant biological behavior of HCC by triggering demethylation of PKM2 mRNA.…”
Section: A Methylation and Metabolic Reprogramming In Tmementioning
confidence: 99%
“…Several studies have demonstrated that m 6 A modulators (e.g., METTL3 and WTAP) affect tumor glucose metabolism by regulating glycolytic enzymes (Warburg effect) to promote proliferation [ 58 60 ]. The glycolytic pyruvate kinase isoenzyme PKM2 (a glycolytic rate-limiting enzyme) is expressed in a variety of cells, particularly tumor cells [ 61 ]. The m 6 A eraser, FTO, accelerates translation and promotes malignant biological behavior of HCC by triggering demethylation of PKM2 mRNA.…”
Section: A Methylation and Metabolic Reprogramming In Tmementioning
confidence: 99%
“…Fittingly, R3hdml knockout in mice show elevated albuminuria, podocyte foot process effacement and GBM thickening. Pyruvate kinase ( Pkm , log 2 FC = 0.87) overexpression in podocytes protects against mitochondrial dysfunction in murine diabetic nephropathy 20 and conversely, its loss worsens albuminuria and podocyte injury in an adriamycin model of focal segmental glomerulosclerosis (FSGS) 21 . Cdkn1c (log 2 FC = 1.04), encoding p57, is associated with podocyte proliferation in animal models of podocyte injury 22,23 and patients with proliferative glomerular disease 24,25 , with upregulation of p57 in cultured podocytes being associated with reduced proliferation rates 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Fittingly, R3hdml knockout in mice show elevated albuminuria, podocyte foot process effacement and GBM thickening. Pyruvate kinase (Pkm, log2FC = 0.87) overexpression in podocytes protects against mitochondrial dysfunction in murine diabetic nephropathy 20 and conversely, its loss worsens albuminuria and podocyte injury in an adriamycin model of focal segmental glomerulosclerosis (FSGS) 21 .…”
Section: Dysregulation Of the Podocyte Transcriptome Dominates Early ...mentioning
confidence: 99%
“…In addition, changes in metabolic fuel sources in diabetes and continuous ATP demand lead to an increase in oxygen consumption, which contributes to renal hypoxia [80]. Indeed, several studies published by King’s group have reported that elevated PKM2 in podocytes, a glycolysis metabolism enzyme, increased glucose flux and protected mitochondrial function, thus alleviating the progression of diabetic glomerular pathology [78, 81, 82]. A recent study highlighted the antiapoptotic potential of PKM2 by upregulating mitochondrial fusion protein Mfn1 [83].…”
Section: Mitochondria Dysfunction In Ckdsmentioning
confidence: 99%